Antecedents of Workplace Energy Saving Behaviour: An Integration of the Theory of Planned Behaviour and Norm Activation Model - Fatoki, Olawale (International Journal of Energy Economics and Policy, 2023)
Hotels are energy intensive facilities and have contributed to environmental problems such as high consumption of natural resources, high emissions of carbon dioxide and waste pollution. Therefore, it is important to understand the factors that can reduce energy (electricity) consumptions in hotels. The study examined the antecedents of employee energy saving behaviour in hotels by integrating the Theory of Planned Behaviour (TPB) and the Norm Activation model (NAM). Data was collected from the respondents through the cross-sectional survey method. The Partial Least Square Structural Equation modelling (PLS SEM) was used to analyse data and test the hypotheses. The results indicated that two TPB constructs (attitude and perceived behavioural control) are significantly positively related to energy saving intention. In addition, three NAM constructs (awareness of consequences, ascription of responsibility and personal norm) are significantly positively related to energy saving intention. Energy saving behaviour is influenced by intention. Recommendations focus on awareness about the negative effects of energy consumption on the environment through education and training.